Experiences of general practice of children with complex and palliative care needs and their families: a qualitative study. Issue 1 (6th January 2021) - Mitchell, Sarah; Harding, Stephanie; Samani, Mohini; Slowther, Anne-Marie; Coad, Jane; Dale, Jeremy
Abstract : Objectives: To investigate the views and experiences of general practice of children with life-limiting and life-threatening conditions, and their family members, through secondary analysis of a qualitative serial interview study. Thematic analysis was conducted on all interview data relating to experiences of primary care. Setting: West Midlands, UK. Participants: A total of 31 participants (10 children with life-limiting and life-threatening conditions and 21 family members) from 14 families. Study design and setting: Secondary thematic analysis of qualitative interview data from a study carried out in the West Midlands, UK. Method: 41 serial interviews with 31 participants from 14 families: 10 children aged 5–18 years with life-limiting and life-threatening conditions, and 21 of their family members. Results: Three key themes emerged: (1) poor experiences of general practice cause children and families to feel isolated, (2) children and families value support from general practice, and (3) there are practical ways through which general practice has the potential to provide important aspects of care. Children and families reported benefits from fostering their relationship with their general practice in order to access important aspects of care, including the assessment and management of acute illness, chronic disease and medication reviews, and holistic support. Conclusion: Children with life-limiting and life-threatening conditions and their families value the involvement of general practice in the care, alongside their paediatric specialists. Ways of developing and providing such support as part of an integrated system of care need to be developed.